Brake Motion Control for Quadruped Hopping Robot by Using Reference Height Control System - Anuar , Mohamed Kassim; Subramonian, Sivarao; Jaafar, Hazriq Izzuan (Praise Worthy Prize S.r.l, 2013)
In this paper, the generation of brake motion control for our developed quadruped hopping robot while moving on two dimensional spaces by jumping continuously is discussed. The braking motion method which is approached is by applying the reference height control system to create the differences of front leg and back leg while making moving performance and correct the body posture which has inclined to make the quadruped hopping robot jump vertically while braking performances. On the other hand, this approached method can be used as the collision-avoidance behavior for the quadruped hopping robot. The MATLAB/Simulink model is used in order to conduct the pattern generation of quadruped hopping robot. As the result, effectiveness of approach method is confirmed to generate brake motion control of quadruped hopping robot while making continuous jumping vertically. Copyright © 2013 Praise Worthy Prize S.r.l. - All rights reserved